Tujuan dan Fungsi Alih Kode Penumpang Terhadap Awak Bus Rute Bojonegoro-Surabaya - Nova Yoga, Sahri (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
This research aims to describe and examine the purpose and function of passenger code switching to bus crew. This data was obtained from the speech of passengers, bus crew and bus drivers. The method used is a qualitative descriptive method where the data is obtained, classified, analyzed and then a general description of the data studied is obtained and uses observation methods in the form of listening techniques, recording techniques, and interview techniques. The results of this study are threefold: (1) the form of variations in the code switching of passengers to bus crew members, (2) the function of code switching of passengers to crew members, and (3) the causes of code switching of passengers to bus crews